Mating and parenting experiences sculpture mood-modulating effects of oxytocin-MCH signaling - Joseph Phan (Nature Portfolio, 2020)
Abstract The two hypothalamic neuropeptides oxytocin and melanin concentrating hormone (MCH) share several physiological actions such as the control of maternal care, sexual behavior, and emotions. In this study, we uncover the role for the oxytocin-MCH signaling pathway in mood regulation. We identify discrete effects of oxytocin-MCH signaling on depressive behavior and demonstrate that parenting and mating experiences shape these effects. We show that the selective deletion of OXT receptors from MCH neurons increases and decreases depressive behavior in sexually naïve and late postpartum female mice respectively, with no effect on sexually naïve male mice. We demonstrate that both parenting experience and mood-regulating effects of oxytocin-MCH are associated with synaptic plasticity in the reward and fear circuits revealed by the alterations of Arc expressions, which are associated with the depressive behavior. Finally, we uncover the sex-dependent effects of mating on depressive behavior; while the sexual activity reduces the basal levels of depressive behavior in male mice, it reduces in female mice evoked-depression only. We demonstrate that the oxytocin-MCH pathway mediates the effects of sexual activity on depressive behavior. Our data suggest that the oxytocin-MCH pathway can serve as a potential therapeutic target for the treatment of major depression and postpartum mood disorders.